ERADICATION OF H.PYLORI: RISK ASSESSMENT AND POSSIBLE PREVENTION OF DRUG-DRUG INTERACTIONS - S. YU. Serebrova; A. B. Prokofev; M. V. Zhuravleva; G. N. Gorodetskaya; N. N. Eremenko; E. A. Smolyarchuk; D. O. Kurguzova (Антибиотики и Химиотерапия)
Modern therapy, aimed at eradication of H.pylori, includes a set of antisecretory and antibacterial drugs and sometimes bismuth preparations. A feature of modern eradication schemes is the 14-day use of antibiotics, prescribed in high daily doses and selected mainly based on microorganism resistance to clarithromycin and metronidazole in the respective region. However, each component of eradication scheme can have rather serious sode effects, as well as affect the bioavailability, biotransformation, excretion, and the potentiation of the effects of the drugs that the patient can take simultaneously with anti H.pylori therapy. The article lists the most serious and common variants of drug-drug interactions of the eradication schemes' components, it gives a description of the mechanism of their development, when applicable. Before the approval official of practical recommendations for the prevention of drug-drug interactions of drugs included in the eradication schemes, commonly available databases containing information about such interactions should be used.